Treatment with Dielectric Barrier Discharge (DBD) plasma restricts Aspergillus niger growth isolated from wheat grain (Baghdad Science Journal, 2023)
Microbiological contamination by fungi impacts the quality and safety of wheat grain storage. This study aimed to evaluate the efficacy of cold plasma in restricting the growth of the fungus, Aspergillus niger, which was isolated from wheat grains. A dielectric barrier discharge (DBD) operating at atmospheric pressure generated cold plasma that was used to treat the fungus, and the impact of this treatment was investigated at various periods  1, 2, 4, 6, and 15 minutes. The results revealed a highly significant decrease in the growth and number of spores of Aspergillus niger compared to the controls. This study revealed an efficient technique for enhancing wheat grain storage that could be a foundation for further large-scale studies.